Assessment of the Debt Relief Program and Need for Preemptive Credit Counseling - Yoonhae Oh (Korea Development Institute (KDI), 2015)
The number of filings for the debt relief program, especially rehabilitation personal bankruptcy of the court, has risen recently. Preemptive credit counseling is needed to help troubled households find solutions that best fit their needs in order to improve the structure of their debt and suppress a further increase of defaults. To this end, accessibility and neutrality of credit counseling should be improved. - Effective rescue of debtors and prevention of further defaults is urgently needed. - Liquidation personal bankruptcy of the court refers to court proceedings for final liquidation of debt. - Debt restructuring allows borrowers to pay their debt with future earnings by rescheduling the debt or reducing the principal. - Borrowers tend to fall into a vicious circle of paying debt with more expensive credit. - The average amount of debt principal increased significantly. So did the share of debtors who owe credit card companies, lending corporations and savings banks, all of which quote much higher interest rates. - Among households in default, 68.5% attempted to pay their debts with credit card cash advances and 11% were unaware of debt relief program options. - Some debtors may favor more flexible private restructuring methods that the CCRS Debt Repayment Plan offers than court proceedings. - Although many debtors seek help from legal agencies, there are no incentives for the firms to recommend anything but court proceedings. - Credit counseling is effective in improving borrowers' debt structure. If borrowers receive debt management assistance before their debt structure deteriorates, they probably will be able to manage their debts successfully. - Unbiased fair credit counseling can complement the management of debt relief program plans by presenting diverse means of debt management appropriate to individual cases. - To facilitate credit counseling, it is critical to increase access to credit counseling and reinforce the neutrality of the service. - It is essential to increase borrowers' access to credit counseling through diverse means. - For the success of the Microfinance Promotion Agency, it is important to have expert counselors to decide which programs best fit the needs of individual borrowers.
Keywords: 330